2019
DOI: 10.1089/jop.2018.0106
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Distribution of Cyclosporine Following Topical Administration of OTX-101 in New Zealand White Rabbits

Abstract: Purpose: Evaluate the ocular distribution, tolerability, and systemic exposure of cyclosporine (CsA) in New Zealand white rabbits following topical administration of OTX-101, a novel, clear aqueous nanomicellar solution developed for the treatment of dry eye disease (DED). Methods: The study design included single-and repeat-dose phases. In the single-dose phase, rabbits received a single instillation of OTX-101 0.05% or CsA ophthalmic emulsion 0.05% (Restasis Ò ; Allergan, Irvine, CA) as a comparator. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The interest in nanomicelles has recently increased with the recent FDA approval of Cequa ® , a cyclosporine based liquid nanomicellar formulation indicated for the treatment of dry eye syndrome. The topical instillation of cyclosporine nanomicelles resulted in an expansive distribution into cornea and conjunctiva the target tissues for the treatment of dry eye syndrome [56]. In addition, the biopharmaceutical potential of nanomicelles has been enhanced by preparing active targeting nanomicelles capable of promoting active transport of drugs in the posterior segments of the eye [57].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in nanomicelles has recently increased with the recent FDA approval of Cequa ® , a cyclosporine based liquid nanomicellar formulation indicated for the treatment of dry eye syndrome. The topical instillation of cyclosporine nanomicelles resulted in an expansive distribution into cornea and conjunctiva the target tissues for the treatment of dry eye syndrome [56]. In addition, the biopharmaceutical potential of nanomicelles has been enhanced by preparing active targeting nanomicelles capable of promoting active transport of drugs in the posterior segments of the eye [57].…”
Section: Discussionmentioning
confidence: 99%
“…19 A preclinical study compared the ocular distribution and tolerability of OTX-101 and CsA 0.05% emulsion in New Zealand white rabbits. 28 Following a single dosing, there was a higher CsA concentration with OTX-101 0.05% compared with CsA 0.05% emulsion in most ocular tissue samples, including the cornea (2.18-fold) and superior bulbar conjunctiva (1.76-fold) with minimal systemic exposure. 28 There was a dose-related increase in CsA with repeat dosing of OTX-101 0.05% and this also resulted in higher concentrations of CsA in ocular tissues and aqueous humor than CsA 0.05% emulsion.…”
Section: Available Ophthalmic Csa Formulationsmentioning
confidence: 92%
“…28 Following a single dosing, there was a higher CsA concentration with OTX-101 0.05% compared with CsA 0.05% emulsion in most ocular tissue samples, including the cornea (2.18-fold) and superior bulbar conjunctiva (1.76-fold) with minimal systemic exposure. 28 There was a dose-related increase in CsA with repeat dosing of OTX-101 0.05% and this also resulted in higher concentrations of CsA in ocular tissues and aqueous humor than CsA 0.05% emulsion. 28 Phase 2b/3 and 3 clinical studies showed that twicedaily administration of OTX-101 0.09% was superior to vehicle in increasing tear production and improving ocular signs from baseline, including conjunctival and corneal staining in patients with KCS.…”
Section: Available Ophthalmic Csa Formulationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Apart from the risk of difficulties associated with topical administration however, more frequent topical instillation to achieve better access to the lacrimal gland [40] raises the possibility of over-correcting an ocular surface imbalance of pro-inflammatory over antiinflammatory cytokines. The problems associated with accessing the lacrimal gland with topical therapy [40] are illustrated by a study involving New Zealand white rabbits and treatment with an aqueous nanomicellar Cyclosporine solution (OTX 101 0.05%) [41]. That study found that after instillation of a single topical drop, the maximum lacrimal gland concentration of Cyclosporine was only 2.7, 2.5 and 1.8% of the corneal, superior bulbar conjunctival and third eyelid concentrations, respectively [41].…”
Section: Treatment Strategies Based On More Refined Disease Classificmentioning
confidence: 99%